A New Transformer‐Less Buck‐Boost Converter With Reliability Assessment Using the Improved Markov Model - Ifham H. Malick; Mohammad Zaid; Javed Ahmad; Chang‐Hua Lin; Marwan Ahmed Abdullah Alasali (Engineering Reports)
ABSTRACT This work proposes a new continuous input current cubic gain buck‐boost converter with a simple structure and reduced components. The converter has minimal components consisting of a twin‐switch configuration with a broad range of duty‐cycle operations. The converter attains unity gain at 24.51% duty cycle and can perform under both the continuous and discontinuous modes of conduction. Adding to the fundamental analysis of the converter, a study to examine the converter's volumetric distribution and cost factor calculation is also discussed. The averaged small‐signal model of the converter is formulated to assess the transfer function and the stability of the converter during its operation. The converter's reliability is also determined to assess its performance using the improved Markov model. The discussion of the variation of the reliability and the MTTF with parameters like the duty cycle of the active switch, input voltage, and output power is also highlighted in the paper. The converter performs at an efficiency of 95.20% while it delivers 100 W output power, making it feasible for low‐ to medium‐power applications. The converter's 200 W hardware prototype is presented, followed by a discussion of the corresponding results. Furthermore, the dynamic state survey of the converter is also presented, where step changes in input voltage, load, and duty cycle are being considered.